Diabetic Macular Edema Treated With Intravitreal Aflibercept Injection After Treatment With Other Anti-VEGF Agents (SWAP-TWO Study)—12-Month Analysis. (October 2020) - Golshani, Cyrus; Conti, Thais F.; Conti, Felipe F.; Silva, Fabiana Q.; Rachitskaya, Aleksandra; Yuan, Alex; Schachat, Andrew; Kaiser, Peter K.; Singh, Rishi P.; Babiuch, Amy
Purpose: This article reports 12-month outcomes of patients with diabetic macular edema previously treated with other antivascular endothelial growth factor agents and transitioned to fixed dosing of intravitreal aflibercept (IAI). Methods: This prospective, single-arm study enrolled patients to receive IAI 2 mg (0.05 mL) every 4 weeks until optical coherence tomography demonstrated no fluid. Patients then received fixed dosing of IAI 2 mg once every 8 weeks through 12 months. Primary outcome was mean absolute change from baseline central subfield thickness (CST) at 12 months measured by optical coherence tomography. Results: Twenty eyes were enrolled. At baseline, best-corrected visual acuity was 70.0 letters, mean CST was 419.7 µm ± 92.0, superficial capillary perfusion density (CPD) was 46.0 ± 4.2%, and deep CPD was 50.8 ± 4.3%. At 12 months, the mean CST improved to 287.2 µm ± 80.2 ( P < .001), superficial CPD decreased to 43.6 ± 4.8% ( P = .04), and deep CPD decreased to 47.6 ± 4.8% ( P = .05). Conclusions: Patients who switched to fixed dosing of IAI demonstrated significant anatomic improvements in CST at 12 months. CPD values decreased significantly both in superficial and deep layers without significant changes in vision.